Infection control in dentistry during COVID – 19 pandemic: what has changed?. Issue 10 (October 2020) - Patel, Mrudula
Abstract: The novel coronavirus (COVID-19) pandemic has emerged disrupting many socio-economical and healthcare aspects across the world. This virus can be transmitted by symptomatic and asymptomatic individuals through saliva and contact. Due to its airborne transmission, aerosols created by natural activities and during dental treatment of infected individuals have become a potential vehicle of transmission and threat. The objective of this review was to assess the existing infection control measures taken in dental health-care settings and suggest modifications to reduce the transmission of novel coronavirus. This is a general review publication. Literature search was made at National Library of Medicine, Pubmed using key words such as "dentistry and COVID", "dentistry and COVID and infection control". Publications related to behaviour, education, ethics, treatment and childcare were excluded. Publications describing general aspects of infection control were reviewed. Keyword "Dentistry and COVID and Infection control" generated 70 publications which were reviewed. Infection control measures in dentistry are designed to minimise cross transmission mainly of blood borne pathogens. The unique nature of COVID-19 including highly infectious and transmissibility, and the ability to survive for a long time in the environment requires special attention and modification to the existing infection control measures which are highlighted here. In conclusion, a modified infection prevention and control (IPC) regime will protect the dental practitioner, assistant and staff, patients and the community. During the pandemic, drastic measures are necessary, however, during an endemic period measures can be remodified as necessary. Abstract : Dentistry; Microbiology; Infection control; COVID-19, SARS-CoV-2; IPC